Process optimization for the production of activated carbon from waste coconut shells in Trinidad & Tobago / Safiyyah N. Wahid... [et.al.] - Wahid, Safiyyah; Maharaj, Rean; Boodlal, Donnie; V. Smith, Jeffrey V. (2023)
Produced water that is generated from the local oil and gas industry is associated with disposal challenges due to the presence of the pollutant phenol in excess of statutory discharge limits. As Trinidad & Tobago (TT) moves towards achieving sustainable development goals of waste minimization and pollution reduction, produced water treatment and reuse, as well as the indiscriminate disposal of waste coconut shells, are receiving national attention due to adverse environmental impacts. In developing countries, activated carbon (AC) made from cheap and abundantly available coconut shells has been successfully used to remove phenol from water by utilizing a packed bed adsorber. The adoption of the packed bed adsorber technology requires critical technical data on the phenol adsorption capacity of the AC manufactured from the waste coconut shells. Moreover, manufacturing AC involves firstly, carbonizing the coconut shells firstly, and then activating them using an oxidizing agent such as carbon dioxide (CO2).